The Efficacy of Tai Chi and Yoga in Rheumatoid Arthritis and Spondyloarthropathies: A narrative biomedical review - AKYÜZ, GÜLSEREN DERYA; KENİŞ COŞKUN, ÖZGE (SPRINGER HEIDELBERG, 2018)
Rheumatoid arthritis (RA) and spondyloarthropathies (SpA) are among the most common inflammatory rheumatic diseases, which might induce chronic pain for their sufferers. Mind-body interventions like Tai Chi and yoga are among the many alternative therapies for combatting chronic pain. This review aims to overview the articles about their effectiveness in RA and SpA. We searched PubMed/MEDLINE, Scopus, and Web of Science for English-language sources from their inception through September 2017. Case-control studies, interventional studies, and case series that included more than three cases and randomized crossover studies were included. The literature search retrieved 133 non-duplicate records, and 15 of them were eligible and were included in this review. The influence of Tai Chi remains debatable in RA, while there is only one study that investigated its efficacy in SpA. Yoga seems effective in decreasing pain and inflammation while increasing quality of life. There are no data available about its effect on SpA. Even after a thorough research, the number of articles is quite limited on the effectiveness of Tai Chi and yoga in RA and SpA. While these complementary approaches still show some promise as alternative therapies in RA and SpA, the literature lacks long-term studies with larger patient groups.
Keywords: Rheumatoid arthritis; Spondyloarthropathies; Tai Chi; Yoga; IYENGAR YOGA; EXERCISE; ADULTS; TRIAL; COMPLEMENTARY; OUTCOMES; PEOPLE; WOMEN; PAIN